The Effect of Sports Sponsorship to Enhance Emerging Digital Marketing Trends in Bayelsa and Delta States - Nathaniel, Nwabuwe Sunday; Okagbare, Tayire Favour; Akarah, Emmanuel Oghenebrorien; Nabofa, Ochuko Eric (Universitas Negeri Makassar, 2026)
This study examined the effect of sports sponsorship in enhancing emerging digital marketing trends in Bayelsa and Delta States, Nigeria. In recent years, sports sponsorship has evolved beyond traditional brand visibility to become a strategic tool for driving digital engagement, audience interaction, and consumer behaviour across online platforms. The study investigated how sponsorship activities in sports influence the adoption of digital marketing strategies such as social media marketing, influencer collaborations, content marketing, and real-time audience engagement among sports organizations and corporate sponsors in the two states. A descriptive survey research design was adopted, targeting sports administrators, marketing executives, athletes, and fans within selected sports organizations and institutions in Bayelsa and Delta States. Data collected were analyzed using descriptive statistics and inferential tools to determine the relationship between sports sponsorship and digital marketing effectiveness. Findings revealed that sports sponsorship significantly enhances brand awareness, online visibility, and customer engagement through digital channels. It also showed that sponsored sports events serve as effective platforms for promoting digital campaigns, increasing social media traffic, and strengthening brand-consumer relationships. However, challenges such as inadequate digital infrastructure, limited technical expertise, and inconsistent sponsorship funding were identified as constraints to maximizing digital marketing benefits. The study concludes that sports sponsorship is a powerful driver of emerging digital marketing trends when effectively integrated with modern digital tools. It recommends improved investment in digital technologies, capacity building for sports marketers, and stronger collaboration between sponsors and digital media platforms to maximize marketing outcomes in the region.